The Precarious Future of Women’s Equality: Access to Justice and the Court Challenges Program - Redford, Vinessa (The Journal of Public Policy, Administration, and Law, 2011)
Until its cancellation in 2006, the Court Challenges Program (CCP) enabled equality-seeking groups to challenge government infringements on the equality rights guarantee in Section 15 (1) of the Canadian Charter of Rights and Freedoms. Through an analysis of twenty-three cases focused on women‘s equality heard by the Supreme Court of Canada between 1985, when the CCP was expanded to fund equality litigation, and 2006, the year of the program‘s cancellation, this article examines how the CCP fostered access to justice. The analysis shows that the CCP funded forty-three per cent of women’s equality litigation in this period. These findings will be of interest to those concerned with the current state of public policy, access to justice, and the advancement of women’s equality in Canada.